(untitled) - Hartmann, Pamela (Boston, 2000)
Quest Second Edition parallels and accelerates the process native-speaking students go through when they prepare for success in a variety of academic subjects. Quest helps students get "up to speed" in terms of both academic content and language skills..The four Listening and Speaking books in the Quest series contain listening and speaking strategies and practice activities centered on authentic recordings from "person on the street" interviews, social conversations, radio programs, and university lectures.. Each student book unit focuses on a different area of university study anthropology, art, biology, business, ecology, economics, history, literature, psychology, and sociology.. . Each chapter contains five parts that blend listening and speaking skills within the context of a particular academic area of study.
Keywords: English language; Texbooks for foreign speakers